FRA SYGDOMSFORTOLKNING TIL SYGDOMSHÅNDTERING I DET ØSTLIGE UGANDA – OG I ANTROPOLOGIEN - Mogensen, Hanne Overgaard (Tidsskriftet Antropologi, 2008)
Medical anthropologists have a long tradition for studying illness explanations offered by local informants as well as how these explanations influence health care seeking behaviour. In spite of anthropologists’ intentions to provide a cultural critique of biomedicine, many studies within medical anthropology actually end up confirming the implicit assumptions of the biomedical paradigm through their focus on local illness explanations and health care-seeking behaviour. Due to their interest in local illness explanations, anthropologists continue to be regarded as those who can identify exotic understandings of sickness. These explanations, it is then assumed, can be turned into more acceptable knowledge and appropriate behaviour through public health initiatives. This article asserts that one way to avoid such a trap is to recognize medical anthropology’s tendency to study the use of cognitive models as analytical framework: classification, semantic networks, explanatory models, narratives etc. There is a definite need for a shift from semantics to pragmatics, when one addresses the interpretation of illness. The discussion is based on fieldwork conducted primarily in Uganda, over the course of the past 15 years. The author’s changes in perspective emerge from developments in anthropology, especially medical anthropology, during this time period.